4DS OF CURRICULUM MODEL, SUSTAINABLE DEVELOPMENT GOALS, AND CURRICULUM ON EDUCATION FOR SUSTAINABLE DEVELOPMENT. (2016)
Most archaeological works in southwestern Nigeria are concentrated in Ile-Ife, Esie, Old Oyo and Owo. In these areas, the focus of archaeological studies had been on different works of art in bronze, terracotta, wood and stone. Studies on cultural themes related to the issues of conflict, war and displacement which have implications for landscape archaeology of the area are often relegated to the background. The main goal of this research was to highlight how conflict, war and displacement impacted on the settlement history of parts of Osun State, southwestern Nigeria. The study also appraised human interactions with the environment and the concomitant effects on emergent settlement configurations. Oral and written data were collected from Ile-Ife, Ikire, Ipetumodu, Ila-Orangun, and Ajaba to generate anthropological data. Investigations aimed at identifying and collecting surface artifacts involved reconnaissance and detailed surveys of the studied sites. Excavations were carried out on potsherd pavements at Ajaba and Asi and on a refuse mound at Ajaba. Artifacts from surface collections and excavations were classified according to types, decoration and functional attributes. Analysis of Mo, Cu, Pb, and Ni of sherd samples was done using inductively coupled plasma mass spectrometry. Ten thin sections were made from selected sherd samples for determination of pottery fabric and inclusions. Palynological analysis of soil samples collected from different depths of the excavated mound was carried out using a microscope with an attached camera. Decorative motifs such as single twisted cord impression were common to all sites. With exception of sherds from Ila-Orangun, those from other areas were related in terms of types, fabric and functional attributes. Some of the sherds bore striking resemblance to those documented for Old Oyo and Ile-Ife with regard to type, decoration and function. Stylistically, the potsherd pavements at Asi and Ajaba were similar to those documented for Ile-Ife. A C-14 date of AD 1263 was obtained from charcoal at a depth of 80cm from the Ajaba mound excavation. Maize cob decoration was absent which indicated that Ajaba site was occupied prior to 16th century when maize was introduced into West Africa. Pollen of forest species and ornamental plants of Asian origin, such as Lagerstroemia indica, Casuarina equisetifolia and Delonix regia was identified from the excavated mound. These were abundant at the lower levels of the excavated mound. However, pollen of ornamental plants disappeared completely at the upper levels while secondary forest species and artifacts increased in abundance which was indicative of increase in human population and subsequent impact on vegetation. There was evidence of increased peopling of the area from around AD 1263. Oral and written records suggested that conflicts and war caused displacement and re-occupation of most of the settlements. Conflict and war resulted in the abandonment and reoccupation of all the sites, resulting in the delineation of several historical phases of occupation. Human impact on the environment was noted from the 13th century.